David MacDonald as a Pioneering Figure in the Study of Overstruck Coins in the Greek World - De Callataÿ, François (KOINON: The International Journal of Classical Numismatic Studies, 2025)
With the passing of David MacDonald (June 26, 1943 – March 29, 2025), the numismatic world has lost a significant figure. Modest to the core and rarely traveling abroad—yet endowed with a sharp sense of humour that he directed as much at himself as at others—Mac (as he was affectionately known) was not a widely familiar figure within the numismatic community. All the more reason, then, to pay him the tribute he truly deserves.